2019
DOI: 10.2337/dc18-1574
|View full text |Cite
|
Sign up to set email alerts
|

Association of Insulin Dose, Cardiometabolic Risk Factors, and Cardiovascular Disease in Type 1 Diabetes During 30 Years of Follow-up in the DCCT/EDIC Study

Abstract: The Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications (DCCT/EDIC) study demonstrated the beneficial effects of intensive therapy on atherosclerosis and clinical cardiovascular disease (CVD) outcomes. The current analyses evaluated the relationship between longitudinal changes in insulin dose and CVD risk factors and outcomes. RESEARCH DESIGN AND METHODS A total of 1,441 participants were randomly assigned to intensive or conventional diabetes therapy during the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 36 publications
(32 reference statements)
3
20
0
Order By: Relevance
“…Additionally, according to the DCCT-EDIC (Epidemiology of Diabetes Interventions and Complications) 9 years of follow-up beyond the end of the DCCT was required to become statistically significant. [30][31][32][33] You may note that although there are internationally well-known scientists who designed these huge trials, there were many unpredicted confounding factors. Although they tried to define the inclusion criteria, additional heterogeneity of their participants in other factors affected the interpretation of their results.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Additionally, according to the DCCT-EDIC (Epidemiology of Diabetes Interventions and Complications) 9 years of follow-up beyond the end of the DCCT was required to become statistically significant. [30][31][32][33] You may note that although there are internationally well-known scientists who designed these huge trials, there were many unpredicted confounding factors. Although they tried to define the inclusion criteria, additional heterogeneity of their participants in other factors affected the interpretation of their results.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Published data from the American Diabetes Control and Complication Trial (DCCT) indicated that a 1.9% decrease in HbA1c through early intensive insulin treatment could significantly decrease the risk of complications and death (36,37). Furthermore, the most recent evidence indicated that large doses of insulin may be associated with adverse cardiovascular outcomes in patients (38). Insulin is therefore a double-edged sword, and should be used in a safe and effective manner.…”
Section: Insulin Injection Guidancementioning
confidence: 99%
“…Patients switching from metformin to an insulin secretagogue, sulphonylurea, have a higher risk of myocardial infarction (MI) 19 . Higher insulin doses are also associated with an unfavorable cardiovascular risk factor profile 20 . No large randomized controlled trials (RCTs) have assessed the role of insulin in CVD, and it may not be ethical to do so.…”
Section: Introductionmentioning
confidence: 99%